2016
DOI: 10.5606/tgkdc.dergisi.2016.11033
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myxoma: a rare cause of acute myocardial infarction

Abstract: Bu çalışmada kardiyak miksomaya bağlı akut miyokard enfarktüsünün klinik özellikleri araştırıldı. Ça lış ma pla nı: Çalışmanın veri kaynağı 01 Ocak 1990 ve 31 Ağustos 2014 tarihleri arasındaki İngilizce literatürden kapsamlı bir veri edinimine dayandırıldı. Kardiyak miksomaya bağlı akut miyokard enfarktüsü olan toplam 48 hasta (ort. yaş 45.2±15.3 yıl; dağılım 9-70 yıl) çalışmaya dahil edildi. Bul gu lar: En yaygın başlangıç semptomu, hastaların %75.6'sında görülen göğüs ağrısı ile akut başlangıç idi. Hastaları… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The incidence of coronary artery disease in patients with myxoma is between 20.3% and 36.6%. [ 2 3 ] Other proposed explanations for the left ventricular dysfunction in such patients were hypercoagulability state in patients with myxoma and raised interleukin-6. [ 3 ] Cases reported by Tewari et al .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The incidence of coronary artery disease in patients with myxoma is between 20.3% and 36.6%. [ 2 3 ] Other proposed explanations for the left ventricular dysfunction in such patients were hypercoagulability state in patients with myxoma and raised interleukin-6. [ 3 ] Cases reported by Tewari et al .…”
mentioning
confidence: 99%
“…Type 1 myxoma is with an irregular villous or papillary surface and a soft consistency, and type 2 myxoma is with a smooth surface and a compact consistency. [ 3 ] Type 1 myxoma is more common and more fragile and tend to embolize frequently than myxomas with a smooth surface. [ 3 ] It is also suggested that repeated impingements of myxoma against the atrial wall or the valve leaflets can form thrombus leading to embolic events.…”
mentioning
confidence: 99%
See 3 more Smart Citations